Regeneration of 'Pera' sweet orange plants through in vitro organogenesis - da Silva, Rosely Pereira; Costa, Maria Angélica Pereira de Carvalho; Souza, Antonio da Silva; de Almeida, Weliton Antonio Bastos (Pesquisa Agropecuaria Brasileira, 2005)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The objective of this work was to establish an efficient protocol for in vitro regeneration of plants through organogenesis of sweet orange 'Pera' (Citrus sinensis L. Osbeck) juvenile explants, in order to give support for future studies of genetic transformation. Epicotyl segments used as explants were introduced in MT culture media. To maximize the regeneration of in vitro plants, experiments were performed to evaluate different concentrations of BAP in the culture media (0, 1, 2, 3 or 4 mg L-1), size (0.25, 0.5 or 1 cm), polarity (basal, medium, and apical), position (horizontal or vertical), luminosity conditions (photoperiod of 16 hours, and darkness for 30 days), and incision of the segment ends. In addition, better conditions for obtaining rooted plants (culture media MT, MT/2, with and without auxin and micrografting) were studied. The combination of 3 mg L-1 BAP with segments of 0.25 cm length was efficient for the organogenetic response. Segment apices and mediums were more efficient comparing to the basal parts. Culturing the segments in the horizontal position, with a photoperiod of 16 hours, was more efficient than in the vertical position. There was no improvement in the induction of in vitro organogenesis, when the explant ends were incised. Micrografting assured 100% of rooted shoots.